(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
It is known that the main part of the existing rivers, canals and other hydro sources have a low pressure. Today, almost all over the world, the use of this hydropower potential for the purpose of generating electricity is of particular interest and is considered an urgent task [1].